Urban Housing Problems And Learning Among Off-Campus Students Of Nasarawa State University, Keffi - Inyang, Martins Nyen; Ejue, Frances Umari; Agwadu, Damian Kunza (Advances in Social Sciences Research Journal, 2018)
Against theoretical evidence postulating a positive relationship between campus residency and collegiate outcomes, prior research has not established a causal link. This study undertook a socio-criminological analysis of Urban Housing problems and learning among off-campus students of Nasarawa State University, Keffi with particular reference to Angwan Lambu Area. The objective of this research was to evaluate the learning implications of off-campus accommodation students. The prevalence of social vices among students living off-campus and their preferences for off-campus accommodation was also examined. Social structure and Anomie theory was used as theoretical justification. The study employed the survey research design. A sample of 214 was drawn from a student population of 25380 using the questionnaire as data collection instrument. Data were collated, analyzed and presented through graphs and charts. Findings revealed that overcrowding, filth and slum-nieghborhoods are the poor living conditions of off-campus Angwan Lambu residences. Cultism, drug dealing and prostitution are some of the social vices common in the area. The study therefore calls on stakeholders by way of recommendations to invest more on students’ accommodation. Security should also be strengthened around off-campus residences that are within the University neighborhood in order to monitor and contain any untoward behavior. The study concludes that learning can be improved and social vices resulting from, and affecting off-campus students can be curtailed where students are provided accommodation and a conducive learning environment by the University Authority either on-campus and/or through private estate developers.